2019
DOI: 10.1055/s-0039-1695021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Dysfunctions and their Associated Factors in Pregnant Women in an Outpatient Prenatal Care Clinic

Abstract: Objective To determine the prevalence of sexual dysfunction and its associated factors in pregnant women. Methods A descriptive, cross-sectional study including 262 pregnant women aged 18 years or older with gestational age between 10 and 35 weeks. Women with urinary tract infections and conditions of gestational risk were excluded. The Pregnancy Sexual Response Inventory (PSRI) questionnaire was used. We performed a univariate descriptive analysis, and comparisons between the mean values of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
0
5
1
6
Order By: Relevance
“…Sexual problems were more prevalent in women who were educated up to tertiary level. This contradicted the findings by Faruk et al [25] and Guendler et al [21] in Turkey and Brazil respectively, who reported that this level of education was associated with reduced risks of sexual dysfunction during pregnancy. Our hypothesis is that since more education could result in better health-seeking behavior, these more educated respondents were better able to identify aberrations in their sexual patterns, and were less reluctant to divulge it.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Sexual problems were more prevalent in women who were educated up to tertiary level. This contradicted the findings by Faruk et al [25] and Guendler et al [21] in Turkey and Brazil respectively, who reported that this level of education was associated with reduced risks of sexual dysfunction during pregnancy. Our hypothesis is that since more education could result in better health-seeking behavior, these more educated respondents were better able to identify aberrations in their sexual patterns, and were less reluctant to divulge it.…”
Section: Discussioncontrasting
confidence: 90%
“…Sexual domains of arousal and orgasm, especially in the last trimester of pregnancy, had the lowest FSFI scores in this study. Previous studies [11,21] also documented low FSFI score in arousal, but higher scores in orgasm. Since majority of the respondents admitted to having sex during pregnancy in order to satisfy their sexual appetite and also claimed sexual satisfaction, the reduction in the FSFI score in orgasm domain in our study may not be unconnected with psychological inhibition which could follow the fear of adverse obstetric outcomes (miscarriage, membrane rupture, infection) reported by the respondents.…”
Section: Discussionmentioning
confidence: 56%
“…Such cases can be due to diabetes-induced psychological problems or the adverse effects of medications used by these patients [9,26]. Sexual desire reduces during pregnancy, especially in the third trimester [1]. Additionally, 80% of women with gestational diabetes do not think about sex, which may be due to their reduced sexual desire following high-risk pregnancy stresses [1].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual desire reduces during pregnancy, especially in the third trimester [1]. Additionally, 80% of women with gestational diabetes do not think about sex, which may be due to their reduced sexual desire following high-risk pregnancy stresses [1]. Psychological changes such as concerns about pregnancy and change in lifestyle and physical symptoms such as fatigue, insomnia, and increased urination can be among other causes of reduced sexual desire [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation